Neuroendocrine Tumours: a Literature Review - K. V. Menshikov; A. V. Sultanbaev; Sh. I. Musin; I. A. Menshikova; A. F. Nasretdinov; N. I. Sultanbaeva; I. R. Shaykhutdinov (Креативная хирургия и онкология)
Neuroendocrine tumours (NETs) are a heterogeneous group of malignant neoplasms with diverse morphology and nomenclature. Well-differentiated NETs were historically termed carcinoid tumours, which entailed abundant confusion and misclassification. Cross body-localised NETs have been described from the central nervous system, respiratory and gastrointestinal tracts, larynx, thyroid, skin, breast and urogenital system. The evidence on NET prevalence is diverse, with selected sources estimating a 0.5% rate among total malignancies diagnosed. Carcinoid syndrome is a known important associate of NETs. Its presence resulting from the amine and peptide hypersecretion often facilitates the NET diagnosis, and curative surgery becomes a treatment of choice, if technically feasible. Adjuvant therapy is ambiguous. When surgery is impractical due to a usually advanced NET at diagnosis, drug therapy is adopted to relief symptoms and control the disease.